2006
DOI: 10.1902/jop.2006.050184
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis Deteriorates Metabolic Control in Type 2 Diabetic Goto‐Kakizaki Rats

Abstract: Our results indicated that PD deteriorates metabolic control in diabetes, which emphasizes that PD may play a significant role for the course of diabetes. The GK rat can represent a suitable model for further studies on the association between PD and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 29 publications
5
33
1
Order By: Relevance
“…It is speculated that NSPT reduces the severity of periodontal infection and decreases the systemic burden of proinflammatory mediators thereby reducing the hyperglycemic state in patients with T2DM [24,25]. However, 6 month follow-up results by Engebretson et al [26] showed no significant improvement glycemic control in patients with T2DM and moderate to advanced periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is speculated that NSPT reduces the severity of periodontal infection and decreases the systemic burden of proinflammatory mediators thereby reducing the hyperglycemic state in patients with T2DM [24,25]. However, 6 month follow-up results by Engebretson et al [26] showed no significant improvement glycemic control in patients with T2DM and moderate to advanced periodontal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolic syndromes associated with increased level of FFA, diabetes, and atherosclerosis have been demonstrated to be highly related to bone loss ( 9, 13 ). More alveolar bone loss is associated with the Goto-Kakizaki rat, a type 2 diabetes rat ( 22 ), and the Zucker fatty rat, a known model of prediabetes ( 23 ). Lower BMD and rapid bone loss is associated with the advanced aortic calcifi cation, a surrogate marker for atherosclerosis, in postmenopausal women ( 24 ), and a graded association is also found between atherosclerotic vascular calcifi cation and vertebral bone loss ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specimens were incubated in a desiccator for 48 hours then coated with platinum and examined under a scanning electron microscope (VEGA II Tescan, Cranberry TWP., PA, USA) at an accelerating voltage of 10 kV. Alveolar bone loss was evaluated morphometrically by measuring the distance between the cemento-enamel junction (CEJ) and the palatal alveolar bone crest (ABC) at nine sites [25] from first to second molar for three times. For each animal, alveolar bone loss was defined as the mean of nine measurements.…”
Section: Methodsmentioning
confidence: 99%